2005
DOI: 10.1111/j.1525-1438.2005.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of lower-dose topotecan in recurrent ovarian cancer: a retrospective case review

Abstract: Topotecan (1.5 mg/m(2)/day for 5 consecutive days of a 21-day cycle) is an established recurrent ovarian cancer treatment, but myelosuppression can be dose limiting. This study evaluates the activity and tolerability of low-dose topotecan in our clinical experience. Case records were reviewed for patients with recurrent ovarian cancer in first through third relapse. Eligible patients had received > or =2 cycles of < or =1.25 mg/m(2) topotecan. Adverse events were evaluated using laboratory and clinical evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Clinical investigations could also benefit from an understanding of the underlying genetic background that determines the activity of topotecan in ovarian cancers (75,76).…”
Section: Functional and Therapeutic Implications Of Mrn And Chk2mentioning
confidence: 99%
“…Clinical investigations could also benefit from an understanding of the underlying genetic background that determines the activity of topotecan in ovarian cancers (75,76).…”
Section: Functional and Therapeutic Implications Of Mrn And Chk2mentioning
confidence: 99%
“…Die schwerwiegende Toxizität ist überwiegend hämatologischer Natur. Mehrere Studien haben niedrigere Anfangsdosen (d. h. 1 bis 1,25 mg/m 2 für 5 Tage alle 21 Tage) vorgeschlagen, um die hämatologische Toxizität zu verbessern 59 60 .…”
Section: Rezidivtherapieunclassified
“…Several noncomparative phase II trials and retrospective reviews of institutional experience in recurrent and resistant ovarian cancer have shown that it is possible to achieve reasonable objective response rates by employing a lower dose (1.0 or 1.25 mg/m 2 ) during a 5-day treatment program [21][22][23], administering the drug on a 3-day regimen [24,25] or delivering the agent on a weekly schedule [26 -28]. In addition, these modified strategies result in a substantial reduction in the toxicities associated with use of topotecan in this palliative clinical setting.…”
Section: Topotecanmentioning
confidence: 99%